Vegetation-Driven Changes in Soil Salinity Ions and Microbial Communities Across Tidal Flat Reclamation - Shumei Cai; Sixin Xu; Deshan Zhang; Yun Liang; Haitao Zhu (Microorganisms, 2025)
Soil microbes play a vital role in tidal flat ecosystems but are highly susceptible to disturbances from land reclamation. This study investigated the dynamics of bacterial communities and their environmental drivers across a 50-year reclamation chronosequence under three vegetation types (bare flats, reed beds, and rice fields). The results showed that, after 50 years of reclamation, total dissolved salts decreased significantly in vegetated zones, particularly in rice fields, where Cl− dropped by 54.71% and nutrients (SOC, TN, TP) increased substantially. Key ions, including HCO3−, Cl−, and K+, were the primary drivers of microbial community structure, exerting more influence than total salinity (TDS) or pH. Bacterial abundance and diversity increased over time, with rice fields showing the highest values after 50 years. Actinobacteriota and Proteobacteria were positively correlated with HCO3− and K+, while Cl− negatively affected Acidobacteriota. Genus-level analyses revealed that specific taxa, such as Sphingomonas and Gaiella, exhibited ion responses diverging from broader phylum-level patterns, exemplifying niche-specific adaptations to salinity regimes. These findings underscore the pivotal role of vegetation type and individual salinity ions in driving microbial succession during tidal flat reclamation. A phased vegetation strategy, starting with reed colonization and followed by rice cultivation, can enhance soil quality and microbial diversity. This research provides important insights for optimizing vegetation management and ion monitoring in sustainable tidal flat reclamation.